FAKTOR RECEIVABLE TURNOVER, CURRENT RATIO DAN DEBT TO EQUITY RATIO TERHADAP RETURN ON ASSET PADA PERUSAHAAN SEKTOR TRADE, SERVICES AND INVESTMENT - Khana Saputri - (Jurnal Ekonomi Bisnis Manajemen Prima, 2021)
This study aims to examine the factors of Receivable Turnover, Current Ratio and Debt To Equity Ratio to Return On Assets in Trade, Services and Investment Sector Companies. The research approach used in this research is quantitative research. The population that will be used in this research is the Trade, Service and Investment companies in the Indonesia Stock Exchange totaling 111 companies with 60 observational data. The results of the research show that Receivable Turnover has no significant effect, Current Ratio has a significant positive effect, Debt to Equity Ratio has a significant positive effect partially. Receivable Turnover, Current Ratio, and Debt to Equity Ratio simultaneously affect Return On Asset in Trade, Service and Investment sector companies listed on the Indonesia Stock Exchange. Meanwhile, the coefficient of determination is 15.9%.